HUMAN RIGHTS PUBLISHING GROUP, The Middle Hour. Selected poems of Kim Chi Ha. Traducidos por David R. McCann con un prefacio de Denise Levertov. Stanfordville, New York, Early M. Coleman Enterprises, Inc., 1980. 88. p. - Romero Castilla, Alfredo (El Colegio de México, 1980)
-